Groundwater recharge sources in semiarid irrigated mountain fronts. Issue 7 (17th January 2020) - Bouimouass, Houssne; Fakir, Younes; Tweed, Sarah; Leblanc, Marc
Abstract: High‐elevation mountains often constitute for basins important groundwater recharge sources through mountain‐front recharge processes. These processes include streamflow losses and subsurface inflow from the mountain block. However, another key recharge process is from irrigation practices, where mountain streamflow is distributed across the irrigated piedmont. In this study, coupled groundwater fluctuation measurements and environmental tracers ( 18 O, 2 H, and major ions) were used to identify and compare the natural mountain‐front recharge to the anthropogenically induced irrigation recharge. Within the High Atlas mountain front of the Ourika Basin, Central Morocco, the groundwater fluctuation mapping from the dry to wet season showed that recharge beneath the irrigated area was higher than the recharge along the streambed. Irrigation practices in the region divert more than 65% of the stream water, thereby reducing the potential for in‐stream groundwater recharge. In addition, the irrigation areas close to the mountain front had greater water table increases (up to 3.5 m) compared with the downstream irrigation areas (<1 m increase). Upstream crops have priority to irrigation with stream water over downstream areas. The latter are only irrigated via stream water during large flood events and are otherwise supplemented by groundwater resources. These changes in water resources used for irrigation practices between upstream and downstream areas are reflected in the spatiotemporal evolution of the stable isotopes of groundwater. In the upstream irrigation area, the groundwater stable isotope values (δ 18 O: −8.4‰ to −7.4‰) reflect recharge by the diverted stream water. In the downstream irrigation area, the groundwater isotope values are lower (δ 18 O: −8.1‰ to −8.4‰) due to recharge via the flood water. In the nonirrigation area, the groundwater has the highest stable isotope values (δ 18 O: −6.8‰ to −4.8‰). This might be due to recharge via subsurface inflow from the mountain block to the mountain front and/or recharge via local low altitude rainfall. These findings highlight that irrigation practices can result in the dominant mountain‐front recharge process for groundwater. Abstract : Groundwater recharge sources in a semiarid irrigated mountain‐front area were investigated using stable isotopes coupled with water table level measurements. Three sources of groundwater recharge were identified: (a) irrigation recharge by diverted streamflow, (b) instream recharge, and (b) subsurface inflow from the mountain block or/and local rainfall infiltration. Among the mountain‐front groundwater recharge components, the irrigation‐induced recharge was revealed as a major source, which could deeply modify both the recharge processes and the water balance in mountain fronts.